Advanced Signal Decomposition Techniques for Vibration Diagnostics in Mechanical Systems: A Fourier-Based Approach - Adel Khalleefah Hamad Darmeesh (African Journal of Advanced Pure and Applied Sciences, 2025)
Vibration analysis plays a critical role in condition monitoring and fault diagnosis of mechanical systems. This paper presents an in-depth investigation into the application of Fourier-based signal decomposition techniques for diagnosing vibrational anomalies in mechanical components. By transforming time-domain vibration signals into the frequency domain using Fourier series expansion and its computational counterpart, the Fast Fourier Transform (FFT) engineers can identify dominant harmonic components that indicate system behavior under dynamic loading conditions. The study outlines the theoretical framework, numerical implementation, and practical applications of Fourier methods in detecting imbalances, misalignments, and structural defects. Additionally, this work explores the integration of these classical tools with modern signal processing strategies to enhance diagnostic accuracy and enable predictive maintenance.